2001
DOI: 10.1097/00001888-200101000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Medical Studentsʼ Awareness of and Sensitivity to Diverse Health Beliefs Using a Standardized Patient Station

Abstract: Cultural competency deficits and differences were measurable using a health-beliefs communications station, and these differences were meaningful enough to warrant faculty discussion and research about how to ensure that students master this competency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 5 publications
0
28
0
Order By: Relevance
“…Four studies reported short and long case scenarios with obviously different durations [11,31,32,37], in contrast to nine studies which did not report station length at all [15,[47][48][49][50][51][52][53][54][55]. Sixteen studies reported references to validity and reliability studies of the assessment forms being used [11,15,24,26,27,30,39,40,[42][43][44][45][46][52][53][54], whilst six studies reported only validity ( [31,33,37,50,55], and twelve reported only reliability [25,28,32,[34][35][36]38,41,[47][48][49]51]. Two studies compared assessments of medical student CS across different institutions [4...…”
Section: Content Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies reported short and long case scenarios with obviously different durations [11,31,32,37], in contrast to nine studies which did not report station length at all [15,[47][48][49][50][51][52][53][54][55]. Sixteen studies reported references to validity and reliability studies of the assessment forms being used [11,15,24,26,27,30,39,40,[42][43][44][45][46][52][53][54], whilst six studies reported only validity ( [31,33,37,50,55], and twelve reported only reliability [25,28,32,[34][35][36]38,41,[47][48][49]51]. Two studies compared assessments of medical student CS across different institutions [4...…”
Section: Content Analysismentioning
confidence: 99%
“…Fourteen papers reported the use of checklists or global rating scales [15,28,29,34,35,38,41,43,45,46,[50][51][52]55], while global rating scales were described in 3 of the 14 papers by Park [34], Wass [43] and Hodges [15], respectively, in Park's paper students were assessed by SP raters only [34]. However we identified 11 papers not reporting any measurement instruments in terms of a documented list of items described in the paper or an appendix [24,25,30,32,36,39,42,44,47,53,54].…”
Section: Content Analysismentioning
confidence: 99%
“…The Cultural Competence in Medicine Questionnaire also measured cognitive outcomes. One diversity assessment, the Robins Health Beliefs Communication OSCE (Robins et al, 2001), measured behavior and one assessment measured the environment, the Elam Diversity in Medical School Questionnaire (Elam et al, 2001).…”
Section: Diversitymentioning
confidence: 99%
“…Currently, many medical schools rely on role-modeling, mentoring, and clinical simulations to convey and provide practice in ACGME/CanMED competencies [11,2326]. However, these methods may create a false sense of measurement when applied to nuanced, context-based behaviors, and may encourage students to ‘perform’ exterior actions rather than function through critically examined internal attitudes [12,19,25,2734]. There remains a need for a dependable means of training and assessing skills within the ACGME- and CanMEDS-mandated domains of medical practice.…”
Section: Introductionmentioning
confidence: 99%